Mature conifers assimilate nitrate as efficiently as ammonium from soils in four forest plantations. Issue 6 (17th December 2020) - Zhou, Xulun; Wang, Ang; Hobbie, Erik A.; Zhu, Feifei; Qu, Yuying; Dai, Luming; Li, Dejun; Liu, Xueyan; Zhu, Weixing; Koba, Keisuke; Li, Yinghua; Fang, Yunting
Summary: Conifers are considered to prefer to take up ammonium (NH4 + ) over nitrate (NO3 − ). However, this conclusion is mainly based on hydroponic experiments that separate roots from soils. It remains unclear to what extent mature conifers can use nitrate compared to ammonium under field conditions where both roots and soil microbes compete for nitrogen (N). We conducted an in situ whole mature tree nitrogen‐15 ( 15 N) labeling experiment ( 15 NH4 + vs 15 NO3 − ) over 15 d to quantify ammonium and nitrate uptake and assimilation rates in four 40‐yr‐old monoculture coniferous plantations ( Pinus koraiensis, Pinus sylvestris, Picea koraiensis and Larix olgensis, respectively). For the whole tree, 15 NO3 − contributed 39% to 90% to total 15 N tracer uptake among four plantations during the study period. At day 3, the 15 NO3 − accounted for 77%, 64%, 62% and 59% by Larix olgensis, Pinus koraiensis, Pinus sylvestris and Picea koraiensis, respectively. Our study indicates that mature coniferous trees assimilated nitrate as efficiently as ammonium from soils even at low soil nitrate concentration, in contrast to the results from hydroponic experiments showing that ammonium uptake dominated over nitrate. This implies that mature conifers can adapt to increasing availability of nitrate in soil, for example, under the context of globalization of N deposition and global warming.